How to anastomose a patch to avoid residual leak in the infarct exclusion method. Issue 3 (30th January 2020) - Kitamura, Hideki; Koyama, Yutaka; Tamaki, Mototsugu; Sawada, Koshi; Kawaguchi, Yasuhiko
Abstract: Background and Aim: Postinfarction ventricular septal defect is a potentially lethal complication of acute myocardial infarction for which surgical repair is mandatory. The infarct exclusion method has contributed to improving surgical outcomes, but a certain percentage of residual leakage continues to be reported. We considered possible mechanisms of residual leakage and modified the sewing method to overcome these mechanisms. Method: A bovine pericardial patch and a Teflon felt strip between the patch and endocardium to achieve good fit were used. The patch and felt were anchored with U stay sutures and reinforced with a running suture. Results: Use of the modified method in seven cases showed improved outcomes. Only one patient had trivial leakage, compared to nine cases using the older method; six of nine patients had residual leaks, including three minor ones. Conclusions: Our method is a rational approach that effectively reduces residual leakage.